Mini Economica Media Komunikasi Ilmu Ekonomi : Pengaruh Pencantuman Perusahaan Dalam Indeks Kompas 100 Terhadap Tingkat Kepemilikan Kas Perusahaan - Permatasari, Elita, Danasari, Dwi Nastiti (Fakultas Ekonomi dan Bisnis Universitas Indones, 2015)
This research is conducted to analyze the effect of firms inclusion in Kompas 10 Index to the level of corporate cash holding. Samples in this research are divided into three categories: all firms, financially constrained firm and financially unconstrained firm, that included in Kompas 100 Index in 2007 and/or 2008. Fixed effects panel data model is used in this research. The result shows that firms inclusion in Kompas 100 Index for all firms, financially constrained firm and financially unconstrained firm significantly affect the level of cash holdings. The evidences also indicate that firm characteristics control variables significantly affect the corporate cash holdings including leverage cash flow, devidend payment, market to book , researcch and development cost, net working capital, capital expenditures, and firms size.